“Digital Visual Literacy”: Case Study of Developing Speaking Textbook - Noor Faridha; Tuminah Tuminah (International Journal of Education, Information Technology, and Others, 2022)
Abstract Several observations were made in the speaking class of first-semester students at the State Administration Study Program, Moch Sroedji University: (1) the lecturers' speaking teaching methods were less varied; (2) the lecturer does not use media/techniques that are related to the theme to be discussed in the speaking course; and (3) learning to speak appears monotonous and boring. Improving literacy through digital visual literacy is one approach. Literacy is defined broadly as the ability to read, write, and count. Visual media literacy can help you develop this ability. In this study, researchers adapted the Gall (2003) model, which includes needs analysis, product development, expert validation, revision, testing, and modification. During the needs analysis stage, researchers interviewed lecturers and students. According to the results of the needs analysis, they require literacy as well as strategies to help them improve their speaking skills.